Design and synthesis of novel 2-(indol-5-yl)thiazole derivatives as xanthine oxidase inhibitors. Issue 6 (15th March 2015) - Song, Jeong Uk; Choi, Sung Pil; Kim, Tae Hun; Jung, Cheol-Kyu; Lee, Joo-Youn; Jung, Sang-Hun; Kim, Geun Tae
Graphical abstract: Compound6k exhibits potent in vitro activities in xanthine oxidase inhibition (IC50 = 3.5 nM). It shows good oral availability and in vivo efficacy in treating hyperuricemic rats. Abstract: Xanthine oxidase (XO) inhibitors have been widely used for the treatment of gout. Indole rings are frequently used as active scaffold in designing inhibitors for enzymes. Herein, we describe the structure–activity relationship for novel xanthine oxidase inhibitors based on indole scaffold. A series of novel tri-substituted 2-(indol-5-yl)thiazole derivatives were synthesized, and their in vitro inhibitory activities against xanthine oxidase and in vivo efficacy lowering uric acid level in blood were measured. Among them, 2-(3-cyano-2-isopropylindol-5-yl)-4-methylthiazole-5-carboxylic acid exhibits the most potent XO inhibitory activity (IC50 value: 3.5 nM) and the excellent plasma uric acid lowering activity. Study of structure activity relationship indicated that hydrophobic moiety (e.g., isopropyl) at 1-position and electron withdrawing group (e.g., CN) at 3-position of indole ring and small hydrophobic group (CH3 ) at 4-position of the thiazole ring enhanced the XO inhibitory activity. Hydrophobic substitution such as isopropyl at 1-position of the indole moiety without any substitution at 2-position has an essential role for enhancing bioavailability and therefore for high in vivo efficacy.